Ethnicity in systemic AL amyloidosis may impact risk stratification - Jahanzaib Khwaja; Sriram Ravichandran; Oliver Cohen; Darren Foard; Ana Martinez – Naharro; Lucia Venneri; Carol Whelan; Philip N. Hawkins; Julian Gillmore; Helen J. Lachmann; Shameem Mahmood; Marianna Fontana; et al. (Haematologica)
Not available.